PENGELOLAAN SUPERVISI AKADEMIK DI SEKOLAH DASAR NEGERI PULAU RIMAU - Kurniati, Meili; Haeriyah, Haeriyah (Graduate Program Magister Manajemen Pendidikan, 2019)
The purpose of this study is to obtain an overview of academic supervision, namely: planning characteristics, implementation characteristics, and characteristics of academic supervision feedback. This research method is qualitative research. Research site at Rimau Island Elementary School in Banyuasin Regency. The technique of collecting data uses observation, interviews, and documentation. Examination of data validity using triangulation techniques. Based on research at SDN Pulau Rimau, the results were: (1) Planning for academic supervision, carried out well by preparing documents, teachers, and instruments. (2) The implementation of academic supervision is carried out democratically and carried out when the teacher conducts learning in the classroom, after which clarification is carried out. (3) Feedback is very important in order to clarify, determine advantages and disadvantages, and provide follow-up in the form of input, guidance, or training.